Krajobraz i jego kulturowa waloryzacja. O przestrzeni znaczącej w Pieninach - Swoboda, Szymon (Zeszyty Wiejskie, 2013)
The article focuses on the problems connected with the local worldview and images concerning the culture and significant space functioning within. The text is a presentation of the part of research results conducted by the author in the Pieniny Mountains from 2009 to 2012. The significant part of the cultural aspects was presented with regard to local mythology (legends and myths), existing terminology and the advantages of the landscape. The author invokes basic landscaping categories – centre and borders. The analysis of the presented ethnographic material, shows the role of particular landscape elements such as: mountains, rocks, stones, valleys, roads, river, forests in the local people worldview. The legends and myths give an explanation to their origin, names and meaning they are given. The aim of the author was also to present and illustrate the culture of the region being discussed – the Pieniny Mountains.